2021
DOI: 10.7150/ijbs.58886
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics reveals heterogeneous progression and EGFR activation in pancreatic adenosquamous carcinoma

Abstract: Pancreatic adenosquamous carcinoma (PASC) — a rare pathological pancreatic cancer (PC) type — has a poor prognosis due to high malignancy. To examine the heterogeneity of PASC, we performed single-cell RNA sequencing (scRNA-seq) profiling with sample tissues from a healthy donor pancreas, an intraductal papillary mucinous neoplasm, and a patient with PASC. Of 9,887 individual cells, ten cell subpopulations were identified, including myeloid, immune, ductal, fibroblast, acinar, stellate, endothelial, and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 81 publications
(91 reference statements)
0
26
0
Order By: Relevance
“…GSE165399 ( 8 ) cohort contained scRNA-seq data of one normal sample (GSM5032773) and two tumor samples (GSM5032771 and GSM5032772). Seurat R package was employed to preprocess single-cell data ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…GSE165399 ( 8 ) cohort contained scRNA-seq data of one normal sample (GSM5032773) and two tumor samples (GSM5032771 and GSM5032772). Seurat R package was employed to preprocess single-cell data ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies (15,31) have shown that ASCP is always more aggressive and malignant histologically than ACP, but previous studies on ASCP (10,14,16) have confirmed that there is no difference in OS between ASCP and ACP in the whole population, which is different from the conclusions reported in the literature (8,12,25). In order to arrive at a reliable conclusion and minimize the influence of various biases, we used PSM to balance the baseline characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our current study is not the first to focus on the single-cell pattern of ASPC. Xin et al reported single-cell sequencing results from one ASPC sample, demonstrating that EGFRassociated ligand-receptor pairs are activated in ductalstromal cell communications (10). However, their study has some questions that need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…S t u di e s f oc u s i n g o n t h e A S P C t u m or microenvironment using single-cell sequencing analysis are also rare, and there is only one study related to ASPC. Xin et al reported single-cell sequencing results from one ASPC sample, demonstrating that epidermal growth factor receptor (EGFR)-associated ligand-receptor pairs are activated in ductalstromal cell communications (10). However, their study lacked a depiction of the ASPC tumor microenvironment and a comparison between PDAC and ASPC.…”
Section: Introductionmentioning
confidence: 99%